Principle and Error Analysis of Non-circular Steel Belt Transmission - Deng Xu; Yuan Ye; Zhang Kai; Wu Qingwen (Jixie chuandong)
Aiming at the problem that the transmission ratio error of a steel belt transmission device in a flexible base is large, the transmission principle and transmission law of the steel belt transmission device are analyzed. Firstly, the non-circular profile of the belt pulley is calculated, and the theoretical transmission ratio and the force characteristics of the steel belt are obtained. Then, a finite element simulation is used to simulate the steel belt transmission, and the effects of local plastic bending of the steel belt and stress concentration at the screw hole on the theoretical transmission ratio are analyzed. Finally, the error analysis of the experimental data of the flexible base is carried out, and the comparison of the experimental data and the simulation data shows that the two have a good agreement. In this study, the influence of belt profile, local plastic deformation and elastic deformation on transmission ratio is analyzed, and on this basis, the improvement scheme is put forward to make the belt transmission become accurate transmission.